Sistem Pendidikan di Belanda - Anggraini, Rani (Faidatuna, 2024)
Education in the Netherlands is the responsibility of the government and is managed by the Ministry of Education, Culture and Science. The Dutch education system is renowned for its holistic approach, which focuses on holistic student development and encourages creativity and critical thinking. The education system in the Netherlands is very different from the education systems known in Asia, America, and even in most parts of Europe. In Europe itself, the Dutch-style education system is only known in a few countries, including Germany and Sweden. One of the differences in the education system in the Netherlands is that majors begin at the elementary level by taking into account the interests and academic abilities of the students concerned